Nutrition therapy in critically ill patients- a review of current evidence for clinicians. Issue 4 (August 2015) - Ridley, Emma; Gantner, Dashiell; Pellegrino, Vincent
Summary The provision of nutrition to critically ill patients is internationally accepted as standard of care in intensive care units (ICU). Nutrition has the potential to positively impact patient outcomes, is relatively inexpensive compared to other commonly used treatments, and is increasingly identified as a marker of quality ICU care. Furthermore, we are beginning to understand its true potential, with positive and deleterious consequences when it is delivered inappropriately. As with many areas of medicine the evidence is rapidly changing and often conflicting, making interpretation and application difficult for the individual clinician. This narrative review aims to provide an overview of the major evidence base on nutrition therapy in critically ill patients and provide practical suggestions.